Potencial biotecnológico de cunninghamella echinulata UCP 1297 na produção de biossurfactante por fermentação submersa - Silva, Nadielly Regina Andrade (2014)
The biosurfactants are a class of compounds obtained by microbial way with amphiphilic molecular structure, responsible for the reduction of surface and interfacial tension, with wide application in the food industry, pharmaceutical, cosmetic, in bioremediation and oil recovery. The search for alternatives to the use of waste makes the production of more viable and competitive biosurfactant minimizing production costs and hence the impact on the environment. In this context, studies were performed with fungus isolated from Caatinga soil (Pernambuco, Brazil). The fungus was identified as Cunninghamella echinulata, being evaluated in a row biotechnological potential biosurfactant production. The growth medium was used agro-industrial residues, corn steep liquor (M) and soybean oil waste (ORS) as substrates, employing a complete planning design of 22 with the variable response biosurfactant production which was evaluated by reduction of the surface tension and emulsification index. The results indicated a reduction of water surface tension of 72 to 36mN/m, and emulsification index of 80% for the engine burning oil. Stability tests with cell-free metabolic liquid against different temperatures, pH and NaCl concentrations for surface tension, as well as the emulsification index. The biosurfactant showed ionic charge, polymeric chemical composition constituted by lipids (40%), carbohydrates (35.2%) and proteins (20.3%), and presented property as ability to oil displacement area and increased or decreased the viscosity. The promising results obtained with the fungus C. echinulata in the of biosurfactant/emulsifier production suggest in future perspectives to use in bioremediation processes, reducing the concentration of the components of petroleum, cleaning tanks, the oil spill, as well as in other industrial applications.